2020
DOI: 10.51451/np.v15i2.64
|View full text |Cite
|
Sign up to set email alerts
|

Ventilación Mecánica Prolongada en Tiempos De Pandemia / Covid-19

Abstract: La pandemia de CoVID-19, puede limitar el recurso en salud en el escenario intrahospitalario para el manejo de pacientes graves, principalmente adultos; por lo cual se deben establecer estrategias desde el ámbito pediátrico, que pueden repercutir consecuentemente en los días camas destinados habitualmente a la población infantil. De los pacientes que emplean ventilación mecánica prolongada, un número importante es manejado en domicilio, siendo considerados de alto riesgo de hospitalización y complicaciones; po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It is worth noting that authors like López Escobar and Zenteno, in their respective studies, concur by identifying Ventilator-Associated Pneumonia (VAP) as the most frequent complication arising from mechanical ventilation. (41,42) Other authors, such as Álvarez Alonso (43) reported an increased incidence of Intraventricular Hemorrhage associated with ventilation in their research. Notably, none of these previously mentioned studies align with the findings of the current study.…”
Section: Resultsmentioning
confidence: 93%
“…It is worth noting that authors like López Escobar and Zenteno, in their respective studies, concur by identifying Ventilator-Associated Pneumonia (VAP) as the most frequent complication arising from mechanical ventilation. (41,42) Other authors, such as Álvarez Alonso (43) reported an increased incidence of Intraventricular Hemorrhage associated with ventilation in their research. Notably, none of these previously mentioned studies align with the findings of the current study.…”
Section: Resultsmentioning
confidence: 93%
“…The acoustic analysis of swallowing, or cervical auscultation (CA) 32 , is an important procedure, in the context of the pandemic, that can be performed rapidly, minimizing the risk of contagion 2 , 6 , 23 . In practice, the sequential relation of swallowing physiology should be kept in mind 33 , as well as interference in the uptake of sounds that may occur due to the respiratory repercussion of COVID-19 and the presence of continuous or discontinuous transmission noise and aggregates, which can make analysis difficult 34 , 35 .…”
Section: Considerations For the Clinical Assessment Of Swallowingmentioning
confidence: 99%